Development of the Export/Import Activities Supply Chain of the Construction Industry of Ukraine - Iryna Markina; Svitlana Tereshenko; Mykhaylo Heyenko; Ihor Kuksa; Irina Shulzhenko (International Journal of Supply Chain Management, 2019)
In this analytical article the information of the construction market of Ukraine in the modern conditions of management is presented. Considered: macroeconomic conditions of market development in the segment of segment analysis, statistics on domestic and foreign markets and expectations of the development of the market of building materials in Ukraine. The analysis of foreign economic supply chain activity of Ukraine on the world market is carried out; the state of Ukraine's integration into the world economy is estimated; the role of foreign investment in Ukraine for the development of international cooperation is defined. The ways of increasing the effectiveness of Ukraine's cooperation with the World Trade Organization (WTO) are determined; prospects of Ukraine's interaction with EU countries are considered.